Diabetes, blood sugar and red wine A personal study. Issue 1 (6th February 2018) - Bland, Martin
Abstract : WhenMartin Bland was diagnosed with type II diabetes, he did what any medical statistician would do: he analysed his blood test results to find out whether alcohol consumption was associated with an increase or decrease in blood sugar levels Abstract : When Martin Bland was diagnosed with type II diabetes, he did what any medical statistician would do: he analysed his blood test results to find out whether alcohol consumption was associated with an increase or decrease in blood sugar levels.